Microfinance and Disasters : Preparing for the Worst - Goldberg, Mike; Varada, Sunita (World Bank, Washington, DC, 2012)
This note discusses natural disaster preparation and how microfinance institutions (MFIs) and their staffs can respond. It is part of a series that summarizes a distance learning series with South American microfinance networks and government officials. Preparation for disaster includes understanding the risks and costs of disasters, establishing proactive approaches and concrete responses, and knowing the resources and partnerships that may prove helpful in an emergency.